Identification of cryodamage on plasma membrane integrity in bull spermatozoa and its relationship with field fertility - Quintero Moreno, Armando; Rubio Guillén, Jorge; González Villalobos, Decio; Gutiérrez, Juan Carlos; Madrid Bury, Ninoska; López Brea, José Julián Garde (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
The aim of this study was to investigate the effect of cryopreservation on the membrane integrity (MI) in the bull sperm, and determine the relationship between intact cryopreserved sperm and field fertility (FF). The eosin nigrosin exclusion and the hypo-osmotic swelling test were combined in a single test (HOS-EN test) to identify the spermatozoa with four types of MI. After cryopreservation, there was a marked decline (21.3%) in the percentage of spermatozoa with head membrane intact/ tail membrane intact (Type IV MI), and a significant increase in those with head membrane damaged/ tail membrane damaged (Type I MI) (P